2021
DOI: 10.1530/eje-21-0561
|View full text |Cite
|
Sign up to set email alerts
|

Shrinkage by the third month predicts long-term response of macroprolactinoma after cabergoline

Abstract: Objective: Transsphenoidal surgery (TSS) is mainly indicated in prolactinomas when dopamine agonist treatment fails. However, there is no established early predictor of cabergoline (CBG) response. The present study was aimed to identify predictors of CBG resistance in order to select patients who may benefit from early TSS. Design: retrospective longitudinal study Methods: We reviewed the medical record of patients diagnosed with prolactinoma after 2010. Inclusion criteria: macroprolactinomas under CBG treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Timing after medical therapy. For macroprolactinomas, MRI should be repeated at 3-6 months after the start of dopamine agonist treatment, as a reduction in size at 3 months after starting cabergoline could predict further long-term response and/or biochemical control 72 . For microprolactinomas, re-scanning depends on clinical and biochemical follow-up, but can be repeated after 1 year, or at least when considering withdrawal of dopamine agonists.…”
Section: Consensus Statementmentioning
confidence: 99%
“…Timing after medical therapy. For macroprolactinomas, MRI should be repeated at 3-6 months after the start of dopamine agonist treatment, as a reduction in size at 3 months after starting cabergoline could predict further long-term response and/or biochemical control 72 . For microprolactinomas, re-scanning depends on clinical and biochemical follow-up, but can be repeated after 1 year, or at least when considering withdrawal of dopamine agonists.…”
Section: Consensus Statementmentioning
confidence: 99%
“…In this regard, the percentage of prolactin reduction could be a more valuable predictor to response to DAs than a predefined cut-off value [73]. We, and others [82], argue in favour of a direct measure of tumour shrinkage response in the third trimester of treatment as an early marker of tumour response. This strategy permits us to take a more individualised decision and not delay foreseeable successful trans-sphenoidal surgery (TSS) in a subgroup of poor responders to DAs with eventual long-term aggressive behaviour [81].…”
Section: Clinical Features Predicting Prolactinoma Response To Damentioning
confidence: 87%
“…Accordingly, it is worthwhile to begin treatment and monitor PRL values and tumor size. It has been reported that the first PRL values obtained during treatment (either evaluated as absolute value or as percent decrease from baseline or as lowering below a predefined threshold, according to different series) as well as early tumor shrinkage (with different cut-offs in different series) are good predictors of long-term DA efficacy ( 120 ), either evaluated at 6 months ( 121 ) or even earlier ( 122 , 123 , 124 ). On the contrary, it was recently reported but not yet confirmed that heterogeneity of prolactinoma T2 signal at diagnosis could be used as a negative predictor factor of hormonal response to DA ( 87 ).…”
Section: Therapeutic Issuesmentioning
confidence: 99%